Peran Media Komunikasi Pemerintahan Dan Perilaku Birokrasi Dalam Pelayanan Publik (Studi Pada Kecamatan Tarogong Kaler Garut) - Muchtar Muchtar; Dody Hermana; Hani Siti Hanifah; Windi Ariesti Anggraeni (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
To realize good governance, it is required that there is a commitment from service providers to provide the best service so that the needs of service recipients can be met, but at the regional level, such as in sub-districts, the community is often faced with conditions that are not very good or bad with public services including procedures for processing ID cards, birth certificates, making land certificates and so on. The object of research in Tarogong Kaler District, Garut Regency. The method in this research is descriptive qualitative which analyzes and describes phenomena or research objects through social activities, attitudes and perceptions of people individually or in groups by using literature studies. The results showed that the low quality of public services in Indonesia is greatly influenced by the poor performance of the bureaucracy where every public service delivery must have service standards and be published as a guarantee of certainty for service recipients which is a measure applied in service delivery that must be obeyed by the service provider and or recipient and the need for a communication media strategy and bureaucratic behavior in public services must correlate with empathy, participation, high achievement motivation, mutual cooperation organizational culture, sharing spirit, conflict climate, and human empowerment.